Penang bridge 1 loading analysis using British standard and finite element method for structural health monitoring - Mohammed, Mohammed Idris; Mustapha, Faizal; Hrairi, Meftah; Sulaeman, Erwin; Mohd Khairol, Anuar; Dyang, Laila; Hojazi, Farzad (2013)
Most existing highway bridges today have been designed to old codes. One of the main highway bridges in Malaysia is Penang Bridge. The cable-stayed Penang Bridge is one such bridge that is adapted to an earlier coding system. This bridge has been designed under British Standards code 153. However, the structure required analysis for compliance to the upgraded British Standards code 5400. The aim of this article is to analyze the Penang Bridge in order to determine the structure’s behavior under the influence of upgraded code traffic loading activity, with the use of structural health monitoring sensing. The conventional traffic loading concept has been used to evaluate bridge elements’ performance with the mentioned code of practice. Four bridge loading scenarios have been investigated. The results clearly show the weak points of bridge’s elements under displacement, deformation, forces, and stress.